Principles of Islamic accounting - Baydoun, Nabil (Singapore : John Wiley & Sons Singapore Pte. Ltd., 2018)
Your introduction to Islamic accounting Principles of Islamic Accounting is the first and only text that covers the fundamentals of Islamic accounting in English. A comprehensive guide, this groundbreaking reference offers both insight into Islamic accounting best practices and disclosure for Shariah-compliant instruments. Covering everything from basic transaction analysis to the preparation of financial statements, this reference serves as a broad framework around which undergraduate students can build their understanding of the Islamic business environment by offering context and showcasing how Islamic values can influence the disclosure of financial information. Islamic accounting is becoming an increasingly important aspect of the business field as globalization results in a surge in business partnerships and transactions around the world. Today's students need to understand Islamic accounting principles in order to effectively work with professionals who adhere to these standards-and accessing this information via text in English was not possible until this revolutionary reference. -Review the basics through an introduction to Islamic accounting -Understand the recording process, and how to complete the accounting cycle and adjust accounts as necessary -Explore accounting for assets, liabilities, equity, and sukuk, as well as zakat and takaful accounting -Discover details regarding Islamic commercial law, accounting for Islamic financial institutions, and Islamic corporate governance and sustainability, and look at auditing from an Islamic perspective Principles of Islamic Accounting is an essential text for first-year university students who are studying Islamic accounting, as well as professional societies and organizations that support the use of Islamic accounting principles, such as The Islamic Finance Professionals Association.
The Islamic accounting environment -- Recording transactions and market values in Islam -- Adjusting Islamic accounting records at the close of the accounting period -- Islamic financial statements OB -- Accounting for Sukuk -- Accounting for Zakat -- Islamic commercial contracts -- Application of Islamic financial contracts to accounting -- Social responsibility accounting.
Includes bibliographical references and index.
Online resource; title from digital title page (viewed on July 25, 2018).
Keywords: Accounting -- Islamic countries; Finance -- Religious aspects -- Islam; Accounting (Islamic law); Electronic books